2021
DOI: 10.1111/jog.14883
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of perfluorooctanoic acid and perfluorooctane sulfonic acid in pregnant women: Maternal predictors and associations with birth outcomes in the PIPA Project

Abstract: Aim: Perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) are persistent pollutants associated with adverse birth outcomes. This study aimed to identify predictors of blood PFOA and PFOS concentrations in pregnant women and to estimate their associations with birth outcomes in Brazil. Methods: We conducted a cross-sectional study with 139 pregnant women enrolled in the pilot study of the Rio Birth Cohort Study on Environmental Exposure and Childhood Development (PIPA Project). Multiple linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Five studies observed a positive predictive relationship between maternal age and maternal plasma [ 87 , 94 ] or serum or plasma neonatal [ 64 , 86 , 91 , 94 ] PFOA concentrations. One study observed a negative relationship between maternal age and PFOA concentrations [ 92 ], though the population was small ( N = 135) and differed geographically from other studies in this review (Brazil). Population sizes for the studies ranged from n = 66 [ 90 ] to n = 5897 [ 94 ].…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Five studies observed a positive predictive relationship between maternal age and maternal plasma [ 87 , 94 ] or serum or plasma neonatal [ 64 , 86 , 91 , 94 ] PFOA concentrations. One study observed a negative relationship between maternal age and PFOA concentrations [ 92 ], though the population was small ( N = 135) and differed geographically from other studies in this review (Brazil). Population sizes for the studies ranged from n = 66 [ 90 ] to n = 5897 [ 94 ].…”
Section: Resultsmentioning
confidence: 80%
“…1 ). The studies were conducted in 15 countries: Canada [ 60 63 ], Taiwan [ 64 ], Norway [ 65 – 71 ], Sweden [ 67 , 72 , 73 ], United States [ 42 , 74 80 ], Slovakia [ 81 ], Japan [ 82 ], Spain [ 83 ], France [ 84 ], Greenland [ 85 ], China [ 86 90 ], Belgium [ 91 ], Brazil [ 92 ], the United Kingdom [ 71 ], and Denmark [ 93 ]. One study evaluated nine European cohorts with data on PFAS concentrations measured in the blood of pregnant mothers or in neonatal cord blood, which was divided into groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations